PENGARUH EMPLOYER BRANDING DAN WEBSITE RECRUITMENT TERHADAP MINAT MELAMAR KERJA DENGAN REPUTASI PERUSAHAAN SEBAGAI VARIABEL MEDIASI STUDI PADA MAHASISWA PROGRAM SARJANA UNIVERSITAS ANDALAS - Ayu Kumala Putri; Herri; Hendra Lukito (Halu Oleo University, 2025)
This study aims to analyse the influence of Employer Branding and Website Recruitment on job application intention with corporate reputation as a mediating variable among undergraduate students of Universitas Andalas. The independent variables in this study are Employer Branding and Website Recruitment, the mediating variable is corporate reputation, and the dependent variable is job application intention. The research was conducted using purposive sampling with a total sample of 234 respondents who are undergraduate students at Universitas Andalas. Data were analysed using the Structural Equation Modelling (SEM) method based on Partial Least Squares (PLS) with the assistance of SmartPLS 4.0 software. The results show that Employer Branding has a positive and significant effect on corporate reputation and job application intention. Website Recruitment also has a positive and significant effect on both corporate reputation and job application intention. Furthermore, corporate reputation has a positive and significant effect on job application intention, and it mediates the relationship between Employer Branding, Website Recruitment, and job application intention. The coefficient of determination (R²) value for corporate reputation is 0.633, meaning that 63.3% of the variation in corporate reputation is explained by Employer Branding and Website Recruitment. Meanwhile, the R² value for job application intention is 0.694, indicating that 69.4% of the variation is explained by Employer Branding, Website Recruitment, and corporate reputation, with the remaining 30.6% explained by other factors beyond the scope of this study.